The Role of Sharia Economic Law in Enhancing the Digitalization of MSMEs: A Systematic Literature Review - Eogenie Lakilaki; Faza Syauqi Amiq; Maulana Jaffar Iqbal; Muhammad Rizky; Nanda Rasinta (Takaza Innovatix Labs Ltd., 2025)
The policy of increasing the Value Added Tax (VAT) rate from 10% to 11% since April 2022 serves as a strategic fiscal instrument for the government to strengthen state revenue, with VAT contributing 30–35% to total national tax revenue. However, the regressive nature of VAT potentially imposes a heavier economic burden on specific segments of society. Low-income households allocate more than 55% of their expenditure to basic needs (food, energy, and transportation). The VAT increase triggers commodity price hikes through a price pass-through mechanism ranging from 60–80%, thereby driving inflation within the administered prices component. This potentially exerts direct pressure on the purchasing power of the poor, reduces consumption volume, and ultimately risks weakening aggregate demand and national economic growth, given that household consumption accounts for over 50% of Indonesia's GDP. Although the government has distributed social assistance (Direct Cash Assistance/BLT, Family Hope Program/PKH, and subsidies) and implemented VAT exemptions on certain basic necessities, the effectiveness and adequacy of these compensatory measures remain a subject of debate. This study aims to provide comprehensive empirical evidence regarding the impact of the VAT rate hike on the purchasing power of low-income households and short-term inflation dynamics in Indonesia. The study employs a descriptive-analytical research approach, using secondary data such as the National Socio-Economic Survey (Susenas), inflation data from Statistics Indonesia (BPS), and a literature review of relevant prior empirical studies. The analysis indicates that the impact of the VAT increase on public welfare is contextual and heavily influenced by the consumption structure of society. This research is crucial for providing fiscal policy recommendations that are fairer, more responsive, and balanced between achieving state revenue targets (fiscal objectives) and protecting the socio-economic welfare of society (public welfare).